The book of Acts in its diaspora setting - Levinskaya, Irina (Grand Rapids, MI Eerdmans, 1996)
Includes bibliographical references and indexes.
File under title so that series is shelved together.
Keywords: Bible. N.T. Acts -- criticism, interpretation, etc; Jewish diaspora; Proselytes and proselyting, Jewish. .; Rome -- religion